PENGARUH PROGRAM PENGELOLAAN SUMBERDAYA HUTAN BERSAMA MASYARAKAT (PHBM) TERHADAP PENDAPATAN PETANI PESANGGEM DI DESA SUKOWIDI KECAMATAN PANEKAN KABUPATEN MAGETAN - Desy Ardiaty Wahyuni (Universitas PGRI Madiun, 2013)
This study aimed to determine the effect of Management of Forest Resources With Society (PHBM) program's, especially PHBM land's on income of pesanggem farmers in Sukowidi Village Sub Panekan Magetan District. Determination of the sample in this study using purposive random sampling which is based on characteristics the Institute of The Forest Village Community (LMDH) Lawu Suko Lestari in Sukowidi Village Sub Panekan Magetan District. The study using a sample of 55 people. The data was collected by questionnaire, interview and documentation. In analyzing the data used statistical method with linier regression test and correlation product moment test. Based on the results of data processing and simultaneous testing on significance level 5% shows that land area of PHBM significant effect on tile income of pesanggem farmers in Sukowidi Village Sub Panekan Magetan District. it is seen from the value of Fhitung (110,079) >= Ftabel (4,02). The influence of variables Management of Forest Resources With Society (PHBM) program's, especially PHBM land's on income of pesanggem fanners it shows with R Square = 0,822 it is means that income influenced by land area 67,56% and while the remaining 32,44% is intluenced by other factors. While results of the T test variable of Management of Forest Resources With Society (PHBM) program's, especially PHBM land's is partiaUy significant effect on income of pesanggem farmers in Sukowidi Village Sub Panekan Magetan District. where variable the land area of PHBM thitung (10,492) >= ttabel (1,673).